Thoracic Surgery during Covid-19 Pandemic; Single Center Experience: Thoracic Surgery during Covid-19 Pandemic - Aytekin Çelik, İlknur; Cınar, Eray; Karaoğlanoğlu, Nurettin (Acta Medica, 2020)
OBJECTIVE After the world health organization declared the Covid-19 epidemic as a pandemic, serious changes were made in the functioning of health institutions along with restrictions in social life. The aim of this study is investigating the operations and clinical procedures performed in a thoracic surgery clinic during covid pandemic. MATERIAL AND METHOD In this study, the surgical procedures performed in the thoracic surgery clinic between March 2020 and June 2020 which is accepted as the first wave dates for Covid-19 in our country are presented. RESULTS Totally, nineteen patients are operated during this period. Average age was 44 (12-68) years old. Forty-three covid PCR tests were performed for a total of 19 patients. Three of them were positive results for Covid-19. After operations one patient died due to septic shock during postoperative period. CONCLUSION Malignancy and emergency surgeries can be performed by following precautions in the outbreak of Covid-19.